2021
DOI: 10.3389/fmars.2021.637030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plastic Debris on the Gut Microbiota of Caretta caretta From Northwestern Adriatic Sea

Abstract: Plastic pollution is nowadays a relevant threat for the ecological balance in marine ecosystems. Small plastic debris (PD) can enter food webs through various marine organisms, with possible consequences on their physiology and health. The loggerhead sea turtle (Caretta caretta), widespread across the whole Mediterranean Sea, is a “flagship species,” useful as indicator of the general pollution level of marine ecosystems. Ingested PD accumulate in the final section of turtles’ digestive tract before excretion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 91 publications
0
19
0
Order By: Relevance
“…The characteristics of plastic elements make them one of the primary pollutants in ecosystems, mainly due to their tendency to fragment into small particles, such as microplastics and nanoplastics [23][24][25][26][27][28]; and by the emission, due to ultraviolet radiation from the sun, of some chemical substances that are added during the manufacturing process (additives) to improve the characteristics of the plastic (e.g., biophenol) [29,30]. Unfortunately, the dumping of plastic waste is a common practice and marine ecosystems have experienced the highest incidence of dumping [31,32], which 2 of 19 affects their flora and fauna [25], and its associated microbiome [33]; as well as their physical environment [34]. Negative externalities have also affected terrestrial ecosystems and agriculture has become a source of pollution, particularly in the case of intensive agriculture due to the massive use of inputs made from plastics [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of plastic elements make them one of the primary pollutants in ecosystems, mainly due to their tendency to fragment into small particles, such as microplastics and nanoplastics [23][24][25][26][27][28]; and by the emission, due to ultraviolet radiation from the sun, of some chemical substances that are added during the manufacturing process (additives) to improve the characteristics of the plastic (e.g., biophenol) [29,30]. Unfortunately, the dumping of plastic waste is a common practice and marine ecosystems have experienced the highest incidence of dumping [31,32], which 2 of 19 affects their flora and fauna [25], and its associated microbiome [33]; as well as their physical environment [34]. Negative externalities have also affected terrestrial ecosystems and agriculture has become a source of pollution, particularly in the case of intensive agriculture due to the massive use of inputs made from plastics [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple factors that may alter the microbiota detected in the feces of sea turtles, including but not limited to health status, diet, age, location, treatment, and debris [46][47][48]. Ahasan et al investigated the effect of antibiotics versus bacteriophage therapy on the fecal microbiota of juvenile green turtles raised in captivity from emergence [46].…”
Section: Fecal Samplesmentioning
confidence: 99%
“…Ingestion of foreign items is a threat to sea turtles and is likely the result of indiscriminate feeding or mistaking foreign objects as food, as such there is growing concern about the effect that plastic may have after ingestion [45]. Ingested plastic debris can act as a vehicle for microbes, chemical pollutants, and toxic compounds [45,47]. Additionally, plastic debris have the potential to cause epithelial damage to the gastrointestinal tract during passage and can result in local inflammation, which may alter the environment within the gastrointestinal tract [47].…”
Section: Fecal Samplesmentioning
confidence: 99%
“…Although these and other studies have provided important glimpses on the interaction processes between the gut microbiome and MPs, the results are mostly focused on model organisms and were obtained under laboratory conditions, exposing mice to MPs comprised of a single polymer and shape at concentrations that might not reflect actual exposure. In a recent study, Biagi et al [48] explored the connections between microbiome composition and gastrointestinal plastic contamination in real-world conditions, i.e., in live loggerhead sea turtles (Caretta caretta) rescued form the Northwestern Adriatic Sea. According to authors, 48 Operational Taxonomic Units (OTUs) showed increased abundance with an increasing plastic content in the feces.…”
Section: Impact Of Microplastics On the Human Gut Ecologymentioning
confidence: 99%
“…The study by Biagi et al [48] indicate that, under real-world conditions, MPs have the potential to affect the gut microbiome, shaping its compositional structure, both directly and indirectly, and facilitating dysbiotic transitions. This evidence, coupled with recent findings showing a relevant MP burden in the human gut, support the importance of quantitatively assessing both the exposure and hazards of MPs in the human gut, allowing for the deduction of real-world risks and outcomes of dybiotic gut microbiome changes.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%